Dystocia due to Breech Presentation of Dicephalus Tetrabrachius Dipus Is chiopagus and Dicaudatus Monster in Buffalo: A Case Report - Dholpuria, Sandeep; Gocher, Trilok; Mehla, Shailendra (Animal Reproduction Update, 2025)
A rare case of conjoined twin monsters (Dicephalus tetrabrachius, Dipus ischiopagus,  and Dicaudatus) was in breech presentation, delivered per vaginum in a pluriparous  Murrah buffalo. The twin monster consists of two male fetuses, each possessing  separate sets of structures, including two heads, two pairs of forelimbs connected to  the ischial region, one pair of hindlimbs, and two tails.
Keywords: Buffalo; dicephalus tetrabrachius; dipus ischiopagus; dicaudatus monster.